The Effect of Problem Posing, CUPs and Critical Thinking on HOTS-Based Learning Achievement - Ika Dewi Lestari; M. Japar; Amalia Sapriati (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aimed to determine the effect of the learning model, which consists of problem posing and conceptual understanding procedures (CUPs) and critical thinking on learning outcomes-oriented (HOTS) on the content of mathematics lessons. The research was conducted at a state elementary school in Jakarta, with a sample of 68 students. The independent variables are learning models and critical thinking, while the dependent variable is HOTS-oriented learning outcomes on the content of mathematics lessons. The method is an experimental method with a 2 x 2 research design. Data were analyzed using normality, homogeneity and Anova tests; Tukey's test was also used as a follow-up test. The results showed: 1) there were differences in the learning outcomes of HOTS-oriented mathematics between students who used the problem-posing learning model and students who used the CUPs learning model; 2) there are differences in HOTS-oriented mathematics learning outcomes between students who have high critical thinking skills and those who have low critical thinking skills; 3) there is an interaction effect between learning models and critical thinking on HOTS-oriented mathematics learning outcomes; 4) there are differences in HOTS-oriented mathematics learning outcomes for students who have high critical thinking skills between those using the problem-posing learning model and the CUPs model; 5) there is no difference in the learning outcomes of HOTS-oriented mathematics students who have low critical thinking skills between those using the problem-posing learning model and the CUPS model. The conclusion of the research is the problem posing learning model and critical thinking skills affect the HOTS-oriented learning outcomes of mathematics lessons. This implies that problem posing and CUPs are effective learning models in improving learning outcomes, so they can be taken into consideration and as new alternatives for teachers.